Fundamental Analysis of the Banking Sector in India - Hanumantha Rao, P.; Dutta, Subhendu (Indian Journal of Finance, 2014)
The last 5-6 years have been very volatile for not only the Indian economy, but also for the entire world economy. Lots of investors have lost their money as the stock prices have fallen flat all over the world during this period. The banking sector has always been one of the important sectors for investment. In the time of uncertainty, when some are arguing that the economies are in the process of recovery, and while others are opining that the world is set for another recession soon, the present article attempted to study the fundamentals of the banking sector in India. The article considered the variables like net operating margin (OPM), net profit margin (NPM), return on equity (RoE), earnings per share (EPS), price earnings ratio (PER), dividends per share (DPS), and dividend payout ratio (DPR) for a period of 6 years from 2006-07 to 2011-12 for three major banks in India - SBI, ICICI Bank, and HDFC Bank. The paper also compared the fundamentals of SBI, ICICI Bank, and HDFC Bank.